The Effect of Obesity, Carbohydrate, and Fat Intake on the Incidence of Type 2 Diabetes Mellitus at the Age of 30-50 Years in Medan - Gifani Anastasya; Fazidah Aguslina Siregar; Taufik Ashar (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Diabetes Mellitus (DM) is a disease that is synonymous with elevated blood glucose levels that have an impact on vascular and nervous system disorders. In 2013, the prevalence of DM in Indonesia was 6.8 percent and increased to 8.5 percent in 2018. North Sumatra is in the twelfth position of provinces in Indonesia with a prevalence of 2 percent and Medan is the city with the highest cases with a total of 249.000 cases. In 2022 in Medan, the number of DM cases is known to be 21,515 cases. This study aims to analyze the effect of obesity, carbohydrate, and fat intake on the incidence of type 2 DM at the age of 30-50 years in Medan. The research method used a case-control unmatching design. The study subjects were aged 30-50 years consisting of 65 DM cases and 65 non-DM as controls. Data analysis was carried out univariate, bivariate, and multivariate with SPSS software using multiple logistic regression tests. The results showed that there was an effect between overweight (p=0.014), carbohydrate intake (p= 0.013), and fat intake (p= 0.032) on the incidence of type 2 DM. Multivariate analysis shows that carbohydrate intake is the most influential variable in the incidence of type 2 DM with an Odds Ratio value of 5.696. It is recommended for the community to carry out a healthy lifestyle by maintaining a diet, and an ideal weight, and exercising regularly. It is hoped that the Posbindu and Prolanis programs can be implemented massively at the community health center. Keywords: Carbohydrate, Fat, Obesity, Type 2 Diabetes Mellitus